(untitled) (Lapai Journal of Economics, 2020)
The study estimated the impact of financial inclusion variables on economic growth in Nigeria for the periods 2006–2018. The variables selected include access to bank credit; number of bank branches; number of automated teller machines/mobile bank users and point of sale (POS). The study adopted the ADF test for stationarity of the variables and ARDL estimation was also conducted to obtain the long and short run coefficients of the variables of the study. On the basis of the result, it was found that access to bank credit has significant positive relationship with GDP growth in Nigeria. The study further concludes that GDP growth has a strong positive relationship with the branch network as well as the number of ATM/ mobile money users/accounts while the relationship between GDP growth and number of POS shows that the number of POS users is weak and has no economic value on the economic growth.The study recommended that government should encourage banks to further increase the number of POS available to customers so as to strengthen the ease of financial access to all bankable persons; also, there is need for banks to increase their number of branches and ATMs in order to enhance access and availability of bank credit to bankable individuals in the country.